2022
DOI: 10.1007/s00068-022-01906-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical stabilization versus nonoperative treatment for flail and non-flail rib fracture patterns in patients with traumatic brain injury

Abstract: Purpose Literature on outcomes after SSRF, stratified for rib fracture pattern is scarce in patients with moderate to severe traumatic brain injury (TBI; Glasgow Coma Scale ≤ 12). We hypothesized that SSRF is associated with improved outcomes as compared to nonoperative management without hampering neurological recovery in these patients. Methods A post hoc subgroup analysis of the multicenter, retrospective CWIS-TBI study was performed in patients with TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Still, recent studies have challenged the role of TBI as a historical contraindication for SSRF, showing the potential benefit of chest wall stabilization in patients with TBI. 15,16,41 Namely, Prins et al reported that in patients with multiple rib fractures and TBI, SSRF was associated with decreased 30-day mortality and lower rates of pneumonia compared with nonoperative treatment. 15 However, while the timing of other surgical procedures in TBI patients has already been investigated-in patients with concurrent TBI and major orthopedic fractures Giannoudis et al 42 recommend early stabilization, as long as hypotension is avoided-no study has investigated the impact of timing to SSRF in this select patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Still, recent studies have challenged the role of TBI as a historical contraindication for SSRF, showing the potential benefit of chest wall stabilization in patients with TBI. 15,16,41 Namely, Prins et al reported that in patients with multiple rib fractures and TBI, SSRF was associated with decreased 30-day mortality and lower rates of pneumonia compared with nonoperative treatment. 15 However, while the timing of other surgical procedures in TBI patients has already been investigated-in patients with concurrent TBI and major orthopedic fractures Giannoudis et al 42 recommend early stabilization, as long as hypotension is avoided-no study has investigated the impact of timing to SSRF in this select patient population.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of the 28 expert panel recommendations were based on low-level evidence, which highlighted an urgent need to generate more robust evidence. For example, a Grade D recommendation that “TBI should not be considered an absolute contraindication to SSRF; patients with TBI be evaluated for SSRF on an individual case basis” spurred a multi-institutional collaborative that has identified which patients with TBI may benefit from undergoing SSRF 17,18 . For other recommendations, nonstandardized ontology may be a barrier for implementing evidence-based practice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a Grade D recommendation that "TBI should not be considered an absolute contraindication to SSRF; patients with TBI be evaluated for SSRF on an individual case basis" spurred a multi-institutional collaborative that has identified which patients with TBI may benefit from undergoing SSRF. 17,18 For other recommendations, nonstandardized ontology may be a barrier for implementing evidence-based practice. For example, many institutional guidelines listed multiple, displaced rib fractures as an indication for SSRF but defined "displaced" heterogeneously.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical stabilization of rib fractures (SSRF) has gained increased popularity during the last decade and has been integrated into current clinical practice with new evidence showing improved outcomes in patients with multiple rib fractures, such as better pain management and superior pulmonary performance 9–11 . While the main indication for SSRF remains flail chest, several recent studies have investigated the role of this operative procedure in patients with different injury patterns, such as nonflail bicortical fractures, showing better pulmonary function test performance and pain management within this population 12–14 …”
mentioning
confidence: 99%
“…[9][10][11] While the main indication for SSRF remains flail chest, several recent studies have investigated the role of this operative procedure in patients with different injury patterns, such as nonflail bicortical fractures, showing better pulmonary function test performance and pain management within this population. [12][13][14] Historically, TBI has been seen as a contraindication to SSRF, and current clinical guidelines cite severe TBI (defined as a head injury with GCS score <8), as an absolute contraindication to surgical rib fixation. 15 A survey conducted among thoracic, trauma, and orthopedic surgeons reported that patients with severe and moderate TBI are less likely to be recommended surgical rib fixation regardless of pulmonary compromise.…”
mentioning
confidence: 99%